A novel carbamide peroxide polymeric nanoparticle bleaching gel: Color change and hydrogen peroxide penetration inside the pulp cavity. Issue 2 (19th September 2020) - Favoreto, Michael W.; Madureira, Mariniella P.; Hass, Viviane; Maran, Bianca M.; Parreiras, Sibelli O.; Borges, Christiane P. F.; Reis, Alessandra; Loguercio, Alessandro D.
Abstract: Objective: This study evaluated the hydrogen peroxide (HP) penetration inside the pulp cavity and the color change of teeth submitted to the 15% carbamide peroxide (CP) nanoparticle bleaching gel at several application times. Materials and methods: Premolars were divided into nine groups (n = 6) according to 15% CP bleaching agents (nanoparticle and commercial) and to application times (15, 30, 45, and 60 minutes). A negative control was exposed to ultra‐purified water. After a whitening procedure, the HP concentration (μg/mL) inside the pulp cavity was assessed via spectrophotometry. The color change (Δ E * and Δ E 00*) was evaluated with a spectrophotometer. Data were analyzed via two‐way ANOVA and Tukey ( α = 0.05). Results: A lower concentration of HP was detected for CP nanoparticle gel after 30 and 45 minutes of whitening procedure ( P = .001). The bleaching groups promoted a higher color change (Δ E * and Δ E 00*) regardless of the application time ( P = .0001). Conclusions: The CP nanoparticle gel reduced HP inside the pulp cavity, and showed effective bleaching compared with CP commercial gel. Clinical significance: Using 15% carbamide peroxide nanoparticle bleaching gel decreased the HP penetration inside the pulp cavity and may decrease bleaching‐induced tooth sensitivity in at‐home bleaching.